PENGARUH SENAM IRAMA TERHADAP KECERDASAN KINESTETIK PADA ANAK DI TK KURNIA ILLAHI KABUPATEN TANAH DATAR - Restu yuningsih; Citra Akmariani; Wahidah Fitriani (Tumbuh Kembang: Kajian Teori dan Pembelajaran PAUD, 2019)
The purpose of this study is to see whether rhythmic gymnastics influences kinesthetic intelligence in early childhood. The formulation of the problem is whether rhythmic exercises affect kinesthetic intelligence in children in Kurnia Illahi Padang Magek Kindergarten, Rambat Subdistrict, Tanah Datar District. This study uses a quantitative approach, pre-experimental research design with type one group pretest-posttest design. In this study the population was children in Kambingia Illahi Padang Magek Kindergarten, Rambat Subdistrict, Tanah Datar District, which consisted of group B, which was a B3 group consisting of 13 children. The treatment given is to use rhythmic gymnastics in developing kinesthetic intelligence. Before the treatment / treatment was given a pretest of kinesthetic intelligence. The average results of pretest13,38. After the pretest was carried out then the treatment was given in the form of applying rhythmic gymnastics, during the treatment there was an increase seen from the posttest results where the average was 24.69. To test the significance of t0 by comparing t0 (t 'count) with tt (' t 'table), if seen in the table of tt value at the level of 5%, the price of criticism is obtained at 2.18. Then the result of t count is 3 , 46> 2.18. Thus, it means that there are significant differences between pretest and posttest in the experimental group. Then the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, meaning rhythmic gymnastics can affect kinesthetic intelligence in children in Kurnia Illahi Kindergarten Padang Magek, Rambat District, Tanah Datar District